Impact of Work-Life Balance, Job Satisfaction, and Stress Levels on Employee Retention in Banking Sector Companies - Titin Herawaty, Mety; Asmadi, Iwan; Rahayu, Eneng Iviq Hairo; Zahra, Zahra (IJBLE Scientific Publications Community Inc., 2024)
This study examines the impact of work-life balance, job satisfaction, and stress levels on employee retention in the banking sector. Utilizing a sample of 300 banking employees, data were collected through structured questionnaires and analyzed using multiple regression analysis. The findings indicate that work-life balance and job satisfaction have significant positive effects on employee retention, while stress levels negatively affect retention. Work-life balance emerged as the strongest predictor of retention, followed by job satisfaction. The results highlight the importance of creating a supportive work environment to improve retention rates in the banking industry. Practical implications suggest that banking companies should focus on fostering employee well-being and reducing workplace stress to retain talent. This study contributes to the existing literature on employee retention by providing insights into the banking sector, offering managerial strategies to reduce turnover, and enhancing overall employee satisfaction.